The belt and road initiative in South Asia : impact, challenges and outlook - Varaha Giri, Avani Giri (2019)
Just when South Asian countries are struggling to address the under-provision of critical infrastructure, China is reaching out to them via the Belt and Road Initiative (BRI), first announced in 2013. As the projects in South Asia increased over the past five years, a number of risks have begun to manifest. The objective of this study is thus to evaluate the varied benefits and risks of the BRI in South Asia, by undertaking nation based case studies and interviews with South Asian academicians, to assess whether South Asian nations have been able to realise the benefits of the venture or not. The study concludes that the BRI has the potential to be a major financier of infrastructure investment in South Asia, but the capturing of this potential by South Asian nations hinges on a number of factors. These include debt sustainability efforts of South Asian countries, India’s position on the BRI and China’s approach to the region. A coordinated effort between China and nations in South Asia could ensure successful implementation of the project in order to meet the region’s social and economic goals.